2016
DOI: 10.1136/bmjopen-2015-008758
|View full text |Cite
|
Sign up to set email alerts
|

Admission to psychiatric hospital in the early and late postpartum periods: Scottish national linkage study

Abstract: ObjectiveTo describe weekly admission rates for affective and non-affective psychosis, major depression and other psychiatric disorders in the early and late postpartum periods. To assess the impact of socioeconomic status, age and parity on admission rates.MethodsScottish maternity records were linked to psychiatric hospital admissions. 3290 pregnancy-related psychiatric admissions were assessed. Weekly admission rates were calculated for the pregnancy period, early postpartum period (6 weeks after birth) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 35 publications
(43 reference statements)
3
31
0
Order By: Relevance
“…The postpartum period confers an increased risk of depression in comparison with other periods in women's lives (Vesga‐Lopez et al, ), but corresponding data in fathers have not been reported. Severe psychiatric morbidity in relation to childbirth, such as postpartum psychosis, postpartum psychiatric admissions, and postpartum suicide, have been described exclusively for mothers (Lindahl et al, ; Munk‐Olsen et al, ; Esscher et al, ; Langan Martin et al, ). It is quite possible that these are unique maternal experiences, but it remains to be established whether the postpartum period is a vulnerability period for severe psychiatric morbidity in fathers also.…”
Section: Maternal and Paternal Depression During Pregnancy And The Pomentioning
confidence: 99%
“…The postpartum period confers an increased risk of depression in comparison with other periods in women's lives (Vesga‐Lopez et al, ), but corresponding data in fathers have not been reported. Severe psychiatric morbidity in relation to childbirth, such as postpartum psychosis, postpartum psychiatric admissions, and postpartum suicide, have been described exclusively for mothers (Lindahl et al, ; Munk‐Olsen et al, ; Esscher et al, ; Langan Martin et al, ). It is quite possible that these are unique maternal experiences, but it remains to be established whether the postpartum period is a vulnerability period for severe psychiatric morbidity in fathers also.…”
Section: Maternal and Paternal Depression During Pregnancy And The Pomentioning
confidence: 99%
“…Since the 19 th Century PP has been widely appreciated as a severe disease, requiring acute intervention. Moreover, epidemiologic studies consistently report a greatly increased risk in psychiatric inpatient admissions within 6 weeks after childbirth compared to any other period in a woman's life . Many of these first‐onset severe postpartum episodes are, in retrospect, the initial presentation of bipolar disorder.…”
Section: Introductionmentioning
confidence: 99%
“…15 It is recognised that women in the early postpartum period (0 to 6 weeks after childbirth) are at particularly elevated risk of requiring psychiatric admission. 16 17 In our previous study, we found that this risk remains elevated for up to 2 years postchildbirth. 16 …”
Section: Introductionmentioning
confidence: 84%
“… 16 17 In our previous study, we found that this risk remains elevated for up to 2 years postchildbirth. 16 …”
Section: Introductionmentioning
confidence: 84%